Improving children’s characters through sirah Nabawiyah concept - Mahriza, Rita; Tursina, Ade; Nadhira, Zahratun (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
This study aims to increase children's character according to the concept of Sirah Nabawiyah through storybooks of the Prophet's stories. The type of research used is classroom action research. This research was conducted in two cycles, each consisting of 4 meetings. Each cycle has four stages: planning, implementation, observation, and reflection. The subjects of this study were seven children consisting of 3 boys and four girls. The data collection technique is an observation sheet, where the observation sheet becomes a research instrument. The study's results were found after conducting this research, so data was obtained starting from the pre-cycle to cycle II, which in the pre-cycle, the children were not independent in carrying out activities, so the results in the pre-cycle were 0%. At the same time, in the first cycle, the children started developing by applying the concepts of sirah nabawiyah through story books. Then in cycle I, it increased by 19.0%, and in cycle II, children grew very well by doing it repeatedly to increase independence gradually to produce the expected indicators. Cycle II increased to 80.9%, which means an increase of 62%. In conclusion, children's character, such as independence, according to the Sirah Nabawiyah concept, has been successful.